Evaluasi Mobile Banking Adoption Intention di BCA dan Variabel-Variabel yang Mendukung Use Behavior - Wijaya, Frans Maharsa (BALANCE: Economic, Business, Management and Accounting Journal, 2023)
ABSTRACTThe number of transactions on BCA's mobile banking channel in 2021 amounted to 61.6% of the total transactions for all media, up 16.8% compared to 2019. There has been a change in preferences for the use of financial transaction facilities by BCA customers. Therefore it is important to study the factors that motivate customers to use BCA mobile banking. This research is a case study that explains the causal relationship between performance expectancy, effort expectancy, social influence, facilitating conditions, habit, hedonic motivation, perceived value, trust, perceived risk, credibility, compatibility with lifestyle and needs and mobile banking adoption intention towards the behaviour of using mobile banking by BCA customers. Questionnaires for this study were distributed to 390 BCA customers and then processed with the help of SPSS and AMOS software using Structural Equation Modeling, data processing using Confirmatory Factor Analysis and regression analysis. The study results show that these factors positively and significantly affect customer intentions to adopt mobile banking. The choice to adopt mobile banking also has a positive and significant impact on customer behaviour when using mobile banking. Further theoretical studies are needed on trust and perceived risk considering that these findings are slightly different from previous studies. It can be examined again regarding the effect of facilitating conditions on mobile banking adoption intention, with moderating variables, namely gender and age.ABSTRAKJumlah transaksi di channel mobile banking BCA pada tahun 2021 sebesar 61,6% dari total transaksi semua channel, naik 16,8% jika dibandingkan tahun 2019. Terjadi perubahan preferensi penggunaan sarana transaksi finansial oleh nasabah BCA. Oleh karena itu penting untuk mempelajari faktor-faktor yang memotivasi nasabah untuk menggunakan mobile banking BCA. Penelitian ini merupakan studi kasus yang menjelaskan hubungan kausal antara performance expectancy, effort expectancy, social influence, facilitating conditions, habit, hedonic motivation, perceived value, trust, perceived risk, credibility, compatibility with lifestyle and needs dan mobile banking adoption intention terhadap perilaku penggunaan mobile banking oleh nasabah BCA. Kuesioner untuk penelitian ini dibagikan kepada 390 customer BCA, kemudian diolah dengan bantuan perangkat lunak SPSS dan AMOS dengan menggunakan Structural Equation Modeling, pengolahan data m manfaatkan Confirmatory Factor Analysis dan analisa regresi. Hasil dari penelitian menunjukkan bahwa faktor-faktor tersebut berpengaruh positif serta signifikan terhadap niat customer untuk melakukan adopsi mobile banking. Niat untuk mengadopsi mobile banking juga berdampak positif serta signifikan terhadap perilaku customer saat menggunakan mobile banking. Perlu kajian teoritik lebih lanjut terhadap trust dan perceived risk mengingat temuan ini sedikit beda dengan penelitian terdahulu. Dapat diteliti kembali mengenai pengaruh facilitating conditions terhadap mobile banking adoption intention, dengan variabel moderasi yaitu jenis kelamin dan usia